Inefficiency caused by random matching and heterogeneity - Kultti, Klaus (2018)
I study an economy with sellers and buyers with unit supplies and unit demands. Both parties have valuations uniformly distributed on a unit interval. I quantify the ineffi ciency, compared to the Walrasian markets, when the agents meet randomly. There are several causes of ineffi ciency that I deal with separately. First, even if there is perfect information about valuations it makes a diff erence whether all agents participate in the markets or whether only those who would trade in the Walrasian market participate. The same applies when there is private information about valuations.